Z Prochowic do Lasu i z powrotem. Z badań nad początkami miasta nad dolną Kaczawą - Boguszewicz, Artur (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article covers the history of the beginnings of the town of Prochowice against the background of the development of settlement along the lower portion of the Kaczawa river during the 13th and first half of the 14th century. Based on the results of archaeological research and analysis of written records, it can be said that the impulse for the construction of the castle in Prochowice, and then in its vicinity the chartered city of Las, was the competition between the Piasts of the Głogów and Legnica lines. After the end of the conflict between the princes, that estate was taken over as a fief of the Legnica princes by the lords from Prochowice, who combined the two domains, transferring their patrimonial name of Parchwitz to the town of Las.
Keywords: Silesian Piasts; nobility; city; Las; Głogów Duchy; Legnica Duchy; Prochowice; middle ages; archaeology; castle